UnCovid: A versatile, low-cost, and open-source protocol for SARS-CoV-2 RNA detection - Roberto Alcántara (Elsevier, 2021)
Summary: Here, we describe a detailed step-by-step protocol to detect SARS-CoV-2 RNA using RT-PCR-mediated amplification and CRISPR/Cas-based visualization. The optimized assay uses basic molecular biology equipment such as conventional thermocyclers and transilluminators for qualitative detection. Alternatively, a fluorescence plate reader can be used for quantitative measurements. The protocol detects two regions of the SARS-CoV-2 genome in addition to the human RNaseP sample control. Aiming to reach remote regions, this work was developed to use the portable molecular workstation from BentoLab.For complete details on the use and execution of this protocol, please refer to Alcántara et al., 2021.